1962
DOI: 10.1111/j.1550-7408.1962.tb02609.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Type of Carbohydrate on Growth and Protein Synthesis by Tetrahymena pyriformis

Abstract: SYNOPSIS. In chemically defined media at carbohydrate concentrations ≧ 0.5% (w/v) Tetrahymena pyriformis W multiplied more rapidly, developed larger cells, and achieved greater growth as measured by optical density when carbohydrate was provided as dextrin rather than glucose. In media containing 0.3 mg/ml of amino acid nitrogen, growth increased with glucose concentration from 0.1 to 1%, did not change significantly to 3%, and was sharply inhibited at higher glucose levels. With dextrin, maximum growth paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1965
1965
1981
1981

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…In rats and chicks, improved growth (1,9,10,15) and nitrogen utilization (30) have been observed when dietary sucrose was replaced by starch or dextrin. We have shown (19) that T . pyriformis also grows faster, achieves greater maximum growth, synthesizes more protein, produces larger cells, and under some conditions, converts medium nitrogen to protein nitrogen more efficiently when carbohydrate is supplied as a polysaccharide rather than as glucose.…”
Section: Ccumulating Evidence Reveals That Carbohydratesmentioning
confidence: 88%
See 2 more Smart Citations
“…In rats and chicks, improved growth (1,9,10,15) and nitrogen utilization (30) have been observed when dietary sucrose was replaced by starch or dextrin. We have shown (19) that T . pyriformis also grows faster, achieves greater maximum growth, synthesizes more protein, produces larger cells, and under some conditions, converts medium nitrogen to protein nitrogen more efficiently when carbohydrate is supplied as a polysaccharide rather than as glucose.…”
Section: Ccumulating Evidence Reveals That Carbohydratesmentioning
confidence: 88%
“…Cells for experimental use were produced in 35 ml quantities of the same media in slanted milk dilution bottles. Preparation of cells for inoculum, growth studies, and other details of methodology were as previously described (19) except for protein-nitrogen estimation. The latter was based on culture optical density which I have shown earlier (18) to be closely correlated with cell protein but not with cell population under the conditions of these experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sucrose, however, failed to support growth of 2 of the strains. Similarly Archibald & Manners(4) observed that cell-free extracts of Tetrahymena pyriformis hydrolyzed sucrose although it is not utilized for growth by this species (13). According to Lewin(9) a mutant of Chlumydomonas dysosmos oxidized acetate to CO2 and Ha, yet acetate did not support its growth.…”
Section: Discussionmentioning
confidence: 99%
“…An abundant supply of motile organisms was a\-ailable always from stock culture or from encysted telas which excysted promptly when stimulated to do so. The osmotic-shock method utilizing distilled water(4) was moderately successful in that it induced excystment of 50 to 70% oi the populations in 24 to 48 hr. Mechanical agitation induced excystmcnt of 90 to IMl% of the populations within [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] min: telas (encysted in a culture tube) were agitated by holding the tube in a I'ortex Jr. mixer (Scientific Industries, Inc.. Springfield.…”
Section: M\teri\ls a S D Methodsmentioning
confidence: 99%